Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
HKS Misinfo Review 2020
DOI: 10.37016/mr-2020-011
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with Others: How the IRA Coordinated Information Operation Made Friends

Abstract: We analyzed the Internet Research Agency's (IRA) 2015-2017 English-language information operation on Twitter to understand the special role that engagement with outsiders (i.e., non-IRA affiliated accounts) played in their campaign. By analyzing the timing and type of engagement of IRA accounts with non-IRA affiliated accounts, and the characteristics of the latter, we identified a three-phases life cycle of such engagement, which was central to how this IRA network operated. Engagement with external accounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
(5 reference statements)
1
12
0
1
Order By: Relevance
“…After Russia's social media influence operations targeting American politics from 2015-2018, a body of research outlined how Internet Research Agency propagandists created fake personas to infiltrate target communities (DiResta et al, 2019;Howard et al, 2018;Linvill & Warren, 2020a;Linvill & Warren, 2020b). Research has shown that people are more receptive to information from in-group members and from sources they deem credible and trustworthy (Pornpitakpan, 2004).…”
Section: Fake Persona Creationmentioning
confidence: 99%
“…After Russia's social media influence operations targeting American politics from 2015-2018, a body of research outlined how Internet Research Agency propagandists created fake personas to infiltrate target communities (DiResta et al, 2019;Howard et al, 2018;Linvill & Warren, 2020a;Linvill & Warren, 2020b). Research has shown that people are more receptive to information from in-group members and from sources they deem credible and trustworthy (Pornpitakpan, 2004).…”
Section: Fake Persona Creationmentioning
confidence: 99%
“…Peaks in account creation times on Twitter and Reddit corresponded to the lead-up to the announcement of the Republican nomination (Zannettou et al, 2019). To avoid detection, profile descriptions of pseudo-accounts were integrated into the target community by posing as news outlets or journalists and US persons affiliated with political parties (Linvill & Warren, 2020;Mueller, 2019).…”
Section: Application Of the Frameworkmentioning
confidence: 99%
“…In Stage 2, the Internet Research Agency's pseudo-accounts used a network-based selection of audiences to identify influential accounts (Linvill & Warren, 2020). They selected audiences through topics of interest, by filtering for hashtags, and by users' self-reported countries (Zannettou et al, 2019).…”
Section: Application Of the Frameworkmentioning
confidence: 99%
See 2 more Smart Citations